A systematic ageing method I: H ii regions D118 and D119 in NGC 300. Issue 1 (14th August 2020) - Stevance, H F; Eldridge, J J; McLeod, A; Stanway, E R; Chrimes, A A
ABSTRACT: Accurately determining the age of H ii regions and the stars they host is as important as it is challenging. Historically, the most popular method has been isochrone fitting to Hertzsprung–Russell diagrams or colour–magnitude diagrams. Here, we introduce a different method for age determination using BPASS (Binary Population and Spectral Synthesis) and hoki . We infer the most likely ages of the regions D118 and D119 NGC 300 to be log(age/yr) = 6.86^+0.05_-0.06 and we also deduce stellar mass and number counts by comparison with the BPASS models. We compare how our binary and single-star models perform and find that the latter are unable to predict 20 per cent (±10 per cent) of our sample. We also discuss how results obtained from isochrone fitting would differ. We conclude that ages could be underestimated by ∼0.2 dex and that the limitations of the isochrone method is not solely due to the lack of binary stars. We propose that the method presented here is more reliable and more widely applicable since it can be used on smaller samples. Alongside this study, we release new hoki features to allow easy implementation of this method.